Differences in post-placental intra uterine device acceptance with and without couples counseling in private practice midwifery clinics, West Denpasar - Putu Ayu Ratna Darmayanti; Dewa Nyoman Wirawan; Komang Ayu Kartika Sari; Mangku Karmaya; Ni Luh Putu Suariyani (Universitas Udayana, 2018)
Background and purpose: The post-placental intra uterine device (IUD) program is one intervention to increase IUD uptake however the acceptance remains low. Contraceptive counseling during pregnancy is expected to increase IUD uptake. The primary objective of this study is to determine the efficacy of counseling by involving the husband in order to improve post-placental IUD uptake. The secondary objective is to compare knowledge and perceptions of IUD before and after intervention. Methods: A randomized controlled trial was conducted with 58 pregnant women at 37-40 weeks’ gestation in three private midwifery clinics in Denpasar, Bali. Subjects were divided into two groups: 29 intervention groups that were given couples counseling and 29 control groups that were given counseling without involving husbands. Base line interview was conducted during enrollment and follow up interview was carried out immediately after delivery. Results: Acceptance of post-placental IUD was found in 21 women (72.41%) in the intervention group and 10 women (34.48%) in the control group (RR=2.2; 95%CI: 1.23-3.84). The mean difference in pretest and post-test scores of knowledge, perceptions of susceptibility and benefits were found to be higher in the intervention group but not statistically significant. The result of multivariate analysis indicated that the variables influencing post-placental IUD acceptance were the child’s gender (AOR=45.9, 95%CI: 4.53-465.25), couples counseling with husband (AOR=17.4, 95%CI: 2.55-119.56) and maternal education (AOR=7.1; 95%CI: 1.17-43.40). Conclusions: Couples counseling was found to increase postplacental IUD uptake. In addition, post-placental IUD acceptance is also influenced by the child’s gender and maternal education levels. To increase uptake of post-placental IUDs there is a need for upscalling of couples counseling at the time of antenatal care.